A narrative analysis of identification of skills needed for management training module development - Rusali, Roszanadia; Md Yusop, Nor Baizura; Ghazali, Hazrina; Omar, Noraida; Jamaluddin, Rosita (Human Resource Management Academic Research Society, 2023)
Practical training can positively impact the individuals management skills and enhance the organization's performance. This study aimed to examine the management skills required by dietitians. Semi-structured face-to-face interviews comprising items emphasizing the skills required by the dietitians were conducted. The interviews were audio-recorded, transcribed, and analyzed using a thematic approach. Five (5) Heads of the Dietetics Department from four government hospitals and one private hospital in Malaysia participated in the study. A needs analysis was carried out to establish the experts opinions on the management skills required by dietitians. Three main themes evaluating the management skills required by dietitians were generated: (1) individual qualities, (2) working with others, and (3) managing services in the organization. Stress and time management, effective communication, dealing with difficult people, motivation, and teamwork, were suggested to produce better quality work. All respondents agreed to develop and implement management skills training among the dietitians. The findings provided the basis for developing a training module, mainly for dietitians who need to perform management tasks at the workplace. Management skills training promotes career development by enhancing morale and increasing productivity. It would also benefit higher education institutions to equip their dietetic students with these management skills to produce competent dietitians upon graduation.